Green Economy-Based Corporate Social Responcibility: A Case Study of PT. Pasangkayu - Firdaus, Muh; Zulkifli, Zulkifli; Jalil, Abdul; Amalia, Rizki (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to analyze how companies can integrate Green Economy principles in the implementation of CSR carried out by the company in order to achieve a balance between business profits, social responsibility, and environmental sustainability. Methodology: The research method used in this research is through a qualitative approach with descriptive methods, with the research subject being PT. Pasangkayu. Data collection techniques using 3 stages, namely: The process of entering the research location, when in the research location, collecting data including: observation, interviews, and documentation. Fundings & Results:  A key finding of this study is the integration between CSR policies and Green Economy principles, demonstrating a dual contribution to community welfare and corporate reputation enhancement. Results:  The results of this study indicate that PT. Pasangkayu has taken proactive steps in integrating sustainability principles into the company's business operations and strategies through 4 priority pillars of CSR programs that focus on community economic empowerment, environmental sustainability, education and health as evidenced by the recap of CSR implementation programs. Novelty & Originality: The novelty of this research lies in its integrative analysis of Green Economy principles and CSR implementation within the palm oil industry, a topic rarely explored in depth. Originality: This study provides insight into the integration of green economic principles in the implementation of corporate social responsibility (CSR) at PT. Pasangkayu. Conclusion: The study concludes that PT. Pasangkayu is committed to sustainable practices through its CSR initiatives, despite facing ongoing social and environmental challenges. Type of Paper: Empirical research Paper.